PERANAN ORGAN VESTIGIAL PADA MAMALIA - dwimei ayudewandari pranatami (Universitas PGRI Adi Buana Surabaya, 2022)
Living things undergo very complex growth and development. Mammals as a class in the kingdom animalia have organ growth, some of which leave residual organs or vestigial organs that still need to be studied more deeply about their role. Vestigial organs are often referred to as evidence of evolution and can be used as markers in the kinship of living things. The existence of vestigial organs in the mammalian body can be found in several places. The purpose of writing this article is to determine the role of vestigial organs in mammals. Many vestigial organs are considered to have no function, even though some of them actually support the survival of these living things. The vestigial organs that can still be found in mammals are: coecum, appendix, third eyelid, auricle muscle, wisdom teeth, splint bone, nails and spine and pelvic girdleThe vestigial organs still have a role even though not in a large part of them; become part of the lymphatic system, move muscles in mechanisms to maintain homeostasis, support other organs in the body and organ development to more complex stages. In addition to the role in this regard, the vestigial organs are still important to study because they are an important part of the growth and development of the body where its existence must have a meaning either to stop during the developmental period or to continue to have a role as long as the vestigial organs are present in the body.